When clients (or psychotherapists) say “I don’t know”: unknowledge or uncertainty? - Zuczkowski Andrzej; Stemberger Gerhard (Gestalt Theory)
Viewing psychotherapy conversations from an epistemic perspective involves analysing how psychotherapist and client manage their knowledge, insufficient knowledge (uncertainty) and lack of knowledge (unknowledge). This article focuses on the use of the epistemic disclaimer “I don’t know”, i.e., a linguistic expressions that speakers employ to indicate uncertainty or unknowledge, in a corpus of psychotherapy sessions. The main aims, both qualitative and quantitative, are to identify the syntactic and pragmatic manifestations of “I don’t know” in the corpus (linguistic analysis), which of them express unknowledge or uncertainty and why (epistemic analisys), how many of them are used by client and psychotherapist respectively. The practical purpose of this study is to give psychotherapists, counselors, clients etc. a few easy criteria for establishing when and why I don’t know communicates uncertainty or unknowledge.